ChatGPT in Education: Ethical Predicaments of Generative AI - Cao, Yalin; Fan, Jinna; Yang, Qian (Transactions on Social Science, Education and Humanities Research, 2024)
ChatGPT, which stands for generative artificial intelligence technology, has become the current prominent topic in the realm of education. The innovative practice of artificial intelligence technology in the field of education has laid a technical foundation for ChatGPT to empower college education, and ChatGPT has also been deeply applied in the fields of educational resource recommendation, language learning support, and personalized learning assistance due to its strong text understanding. It brings vast opportunities for the development of high-quality education, whilst also generating ethical risks for its use. Based on the perspective of educational ethics, this study finds that the ethical problems of generative AI education are mainly reflected in the weakening of the stability of the teacher-student relationship, the impact of privacy protection, and academic misconduct caused by improper human-computer interaction. Accordingly, this paper proposes a series of strategies to alleviate educational ethics from multiple perspectives, such as reconstructing the institutional ethics of data governance, improving the policy system, and strengthening the dominant position of students, so as to guide teachers and students in colleges and universities to maintain rational thinking, prudently use new technologies such as ChatGPT, and promote the development of intelligent education in the new era in the direction of standardized and orderly, human-machine coexistence.